Мезолит Волго-Окского междуречья: технологический подход - Лозовский, В.М.; Гиря, Е.Ю.; Кравцов, А.Е. (Археологический альманах, 2009)
This paper presents findings on technological studies of Mesolithic settlements in the Volga-Oka region (Central Russian Plain). Three settlements were chosen for this analysis: Petrushino 1, complex 2 (Butovo Mesolithic Culture); Ladyzhino 3-a (Yenevo Mesolithic Culture); and Mesolithic layers of Zamostje 2 site.